Pengaruh Pengalaman, Orientasi Etika, Komitmen dan Budaya Etis Organisasi pada Sensitivitas Etika Auditor Badan Pengawasan Keuangan dan Pembangunan Perwakilan Provinsi Bali - Purnama Dewi, Putu; Ramantha, I Wayan; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
T his research examines the influence of experience, ethical oriented, commitment and ethical culture organization towards sensitivity of an auditor of the finance and development supervisor agency (BPKP),Bali representative . Number of respondents taken in this research were 60 respondents. Data was obtained through questionnaire by distributing it to the auditors of the finance and development supervisor agency (BPKP) . Multiple linear regression analysis was used within this research .This research indicates that auditors experiences have no significant effects on their sensitivity. Idealism has positive impacts on the sensitivity of an auditor, whereas relativism has negative impacts on the sensitivity of an auditor in the finance and development supervisor agency (BPKP). Professional commitment has positive impacts on the sensitivity of an auditor. Organizational commitment also has positive impacts on the sensitivity of an auditor of the finance and development supervisor agency (BPKP). Ethical Culture of organizations do have a positive influence to the sensitivity of an auditor of the finance and development supervisor agency (BPKP).
Keywords: sensitivity of ethics, experience, idealism, relativism, professional commitment, organizational commitment, ethical culture organization